Healthy city construction in Liaoning province, 2019: an entropy weight based TOPSIS evaluation - Haijun CAO; Meng WANG (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To comprehensively evaluate the construction of healthy city in Liaoning province for providing evidences to sustainable promotion of healthy city construction. Methods The data for the evaluation were mainly collected from statistics yearbook 2020 of Liaoning province and its 14 municipalities and health report of Liaoning province - 2019. According to the "Healthy China 2030 Plan Outline" and related studies，we build a healthy city evaluation system which includes 5 primary metrics (healthy environment， society，people, industry and healthcare service) and 17 secondary metrics. Using Delphi method, 15 experts were engaged in multiple consultations to assess the healthy city construction of the 14 municipalities with the metrics. The entropy weight method (EWM) was adopted to determine the weights of the metrics. The technique for order preference by similarity to ideal solution (TOPSIS) model was used to evaluate health city construction in 14 municipalities of the province in 2019. Results The implementation of healthy city construction was imbalanced among the 14 municipalities in the year. The results of comprehensive evaluation showed that the 14 municipalities' healthy city construction could be graded into three categories relatively: the capital city (Shenyang) was at the highest level (with an overall index value of 0.5850), followed by the four cities at a moderate level (with the overall index values of 0.51567 - 0.45626) and other 9 cities at lower level (with the overall index values of 0.3704 - 0.2487), respectively. Conclusion The healthy city construction in 2019 was generally well implemented in Liaoning province，but the implementation was imbalanced among the 14 municipalities and among various respects of the construction.